2016
DOI: 10.3168/jds.2015-10398
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of udder health parameters and risk factors for clinical mastitis in Dutch dairy herds in the context of a restricted antimicrobial usage policy

Abstract: Recently, many changes have been implemented in Dutch dairy herds. Herd sizes have increased and antimicrobial use has been reduced. Certain types of antimicrobials can only be used in specific circumstances, and the preventive use of antimicrobials in dry cows is prohibited. The aim of this study was to quantify clinical mastitis (CM), subclinical mastitis (SCM), and risk factors associated with CM in Dutch dairy herds in 2013, in the context of these changes. For this study, 240 dairy herds were randomly sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 46 publications
5
57
1
Order By: Relevance
“…A more realistic aim of a potential new national udder health and AMU improvement program would therefore be to reduce AMU while keeping the country’s udder health status constant. This was only the second preferred aim of both farmers and veterinarians but such achievements are feasible (24, 41). AMU and udder health are highly correlated (9, 10, 14), and any efforts to control mastitis by enhancing prevention and non-antimicrobial intervention strategies are therefore assumed to result in a decrease in AMU.…”
Section: Discussionmentioning
confidence: 99%
“…A more realistic aim of a potential new national udder health and AMU improvement program would therefore be to reduce AMU while keeping the country’s udder health status constant. This was only the second preferred aim of both farmers and veterinarians but such achievements are feasible (24, 41). AMU and udder health are highly correlated (9, 10, 14), and any efforts to control mastitis by enhancing prevention and non-antimicrobial intervention strategies are therefore assumed to result in a decrease in AMU.…”
Section: Discussionmentioning
confidence: 99%
“…It is repeatedly shown that a cut-off of approximately 200000 to 250000 cells per mL is optimal to reduce diagnostic error (Dohoo and Leslie, 1991;Schepers et al, 1997). Many studies used a cut-off of 200000 cells/mL (Schukken et al, 2003;De Vliegher et al, 2004;Svensson et al, 2006;Fouz et al, 2010;Madouasse et al, 2012;Lam et al, 2013;Fauteux et al, 2014;Santman-Berends et al, 2016), while especially for heifers, IMI cut-offs of 150000 cells/mL (Santman-Berends et al, 2016) and 100000 cells/mL (Bludau et al, 2014) have been used. In our study, due to the available data, a preset threshold of 250000 cells/mL was utilized.…”
Section: Introductionmentioning
confidence: 99%
“…For many years, approximately 60% of AMU in dairy cattle was related to mastitis, of which roughly two-thirds could be assigned to dry cow treatment (DCT; Kuipers et al, 2016). Since the ban on preventive use of antimicrobials, blanket DCT (BDCT) has been replaced by selective DCT (SDCT;Santman-Berends et al, 2016). To optimize AMU in the Netherlands, including the introduction of SDCT, farmers and veterinarians have a shared responsibility that is reflected in a compulsory one-on-one relationship between them that was introduced as part of the new legislation (Speksnijder et al, 2015b); together, they have to make a herd health plan and a herd treatment plan, which is based on the actual herd situation.…”
Section: Introductionmentioning
confidence: 99%